Percutaneous Endoscopic Gastrostomy in Children: An Update to the ESPGHAN Position Paper. Issue 3 (September 2021) - Homan, Matjaž; Hauser, Bruno; Romano, Claudio; Tzivinikos, Christos; Torroni, Filippo; Gottrand, Frédéric; Hojsak, Iva; Dall'Oglio, Luigi; Thomson, Mike; Bontems, Patrick; Narula, Priya; Furlano, Raoul; et al.
ABSTRACT: Background: The European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) position paper from 2015 on percutaneous endoscopic gastrostomy (PEG) required updating in the light of recent clinical knowledge and data published in medical journals since 2014. Methods: A systematic review of medical literature from 2014 to 2020 was carried out. Consensus on the content of the manuscript, including recommendations, was achieved by the authors through electronic and virtual means. The expert opinion of the authors is also expressed in the manuscript when there was a lack of good scientific evidence regarding PEGs in children in the literature. Results: The authors recommend that the indication for a PEG be individualized, and that the decision for PEG insertion is arrived at by a multidisciplinary team (MDT) having considered all appropriate circumstances. Well timed enteral nutrition is optimal to treat faltering growth to avoid complications of malnutrition and body composition. Timing, device choice and method of insertion is dependent on the local expertise and after due consideration with the MDT and family. Major complications such as inadvertent bowel perforation should be avoided by attention to good technique and by ensuring the appropriate experience of the operating team. Feeding can be initiated as early as 3 hours after tube placement in a stable child with iso-osmolar feeds of standard polymeric formula. Low-profile devices can be inserted initially using the single-stage procedure or after 2–3 months by replacing a standard PEG tube, in those requiring longer-term feeding. Having had a period of non-use and reliance upon oral intake for growth and weight gain—typically 8–12 weeks—a PEG may then safely be removed after due consultation. In the event of non-closure of the fistula the most successful method for closing it, to date, has been a surgical procedure, but the Over-The-Scope-Clip (OTSC) has recently been used with considerable success in this scenario. Conclusions: A multidisciplinary approach is mandatory for the best possible treatment of children with PEGs. Morbidity and mortality are minimized through team decisions on indications for insertion, adequate planning and preparation before the procedure, subsequent monitoring of patients, timing of the change to low-profile devices, management of any complications, and optimal timing of removal of the PEG.